Binding of ABI4 to a CACCG motif mediates the ABA-induced expression of the ZmSSI gene in maize (Zea mays L.) endosperm - Hu, Yu-Feng; Li, Yang-Ping; Zhang, Junjie; Liu, Hanmei; Tian, Mengliang; Huang, Yubi (Journal of experimental botany, 2012)
Starch synthase I (SSI) contributes the majority of the starch synthase activity in developing maize endosperm. In this work, the effects of various plant hormones and sugars on the expression of the starch synthase I gene (ZmSSI) in developing maize endosperms were examined. The accumulation of ZmSSI mRNA was induced using abscisic acid (ABA) but not with glucose, sucrose, or gibberellin treatment. To investigate the molecular mechanism underlying this effect, the ZmSSI promoter region (-1537 to +51) was isolated and analysed. A transient expression assay in maize endosperm tissue showed that the full-length ZmSSI promoter is activated by ABA. The results of deletion and mutation assays demonstrated that a CACCG motif in the ZmSSI promoter is responsible for the ABA inducibility. The results of binding shift assays indicated that this CACCG motif interacts with the maize ABI4 protein in vitro. The overexpression of ABI4 in endosperm tissue enhanced the activity of a promoter containing the CACCG motif in the absence of ABA treatment. Expression pattern analysis indicated that the transcription pattern of ABI4 in the developing maize endosperm was induced by ABA treatment but was only slightly affected by glucose or sucrose treatment. Taken together, these data indicate that ABI4 binds to the CACCG motif in the ZmSSI promoter and mediates its ABA inducibility.